2000
DOI: 10.1136/heart.83.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative evaluation and surgery in isolated ventricular septal defects: a 21 year perspective

Abstract: Objective-To study short and long term results after surgical closure of isolated ventricular septal defects (VSDs) from 1976 to 1996, especially in relation to changes in preoperative evaluation during this period. Design-Retrospective study. Setting-Tertiary referral centre for paediatric cardiac care. Patients-All children under 18 years of age who had corrective surgery for VSD between 1976 and 1996. Main outcome measures-Preoperative evaluation, indications for surgery, diagnostic errors, and early and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 38 publications
0
45
2
Order By: Relevance
“…28 More recent studies have shown residual defects in 31% of patients and an incidence of complete heart block of 3.1%. 29 Another natural history study showed occurrence rates for pacemaker placement of 9.8 per 10 000 patient-years and occurrence rates for endocarditis of 16.3 per 10 000 patientyears in operated patients. 30 …”
Section: Surgical Closurementioning
confidence: 99%
“…28 More recent studies have shown residual defects in 31% of patients and an incidence of complete heart block of 3.1%. 29 Another natural history study showed occurrence rates for pacemaker placement of 9.8 per 10 000 patient-years and occurrence rates for endocarditis of 16.3 per 10 000 patientyears in operated patients. 30 …”
Section: Surgical Closurementioning
confidence: 99%
“…Currently, pre-natal diagnosis of VSD is relatively difficult and surgical treatment of VSds carries both mortality and morbidity risks, even though it is the most common open heart procedure performed in pediatric cardiac surgery (11,12). The heart is the first organ to form during embryogenesis, and its development is controlled by a series of important genes (13).…”
Section: Discussionmentioning
confidence: 99%
“…In 1954, Lillehei and associates performed the first surgical closure of a congenital ventricular septal defect [3]. Since then, surgical closure has been regarded as the gold standard treatment, albeit it remains associated with morbidity and mortality, postoperative discomfort and the need for sternotomy and a residual scar [4,5]. Because of the complications associated with surgical closure, percutaneous closure has been advocated and in 1988 Lock et al [6] reported the first human experience of transcatheter closure of muscular defects.…”
Section: Introductionmentioning
confidence: 99%